TWIN TRAWLING FOR SHRIMP WITH DUMMY DOOR - RAMARAO, S V.R; MATHAI, P GEORGE; PANICKER, P A (Fishery Technology, 2017)
Twin trawling; a new concept in shrimp trawling is described in this paper. lt essentially involves towing of two trawls of equal size connected in sequence at the inner head and foot rope legs and using a pair of outer otter boards and central neutral door or dummy door with triple bridles and single tow warp. A comparative study with conventional stern trawling using a standard 13.7 m. four seam shrimp trawl and two 6 8 m. standard four seam trawls as twin-â€¢1g has shown considerable reduction in Lle utilizat.un cf 1–ower (20 %) with better eft!ciency in shrimp fishing.